Diagnosis and Management of Patients with Radiation Colitis - Made Bayu Agastia Rakateja; Budi Widodo (Universitas Airlangga, 2023)
Radiation colitis (Radiation Proctitis or Proctopathy) is a condition in which injury to the rectal mucosa is induced by radiation therapy to the pelvic organs. Radiation colitis is a condition that progresses and is becoming more common and dangerous—usually occurring 6 months to 5 years following regional radiation. This paper presented the diagnosis and management of patients with radiation colitis. There was a patient who had cervical cancer and was hospitalized every 2-3 months because of red blood chapters and weakness. She did chemotherapy and radiation for one year. The patient also received medical therapy, including rectal administration of sucralfate and oral sulfasalazine. Management of patients with radiation colitis is still a problem. There are no definite and consistent guidelines for the treatment of radiation colitis In this patient's case, medical therapy was recently carried out, including rectal administration of sucralfate and oral sulfasalazine. The patient was planning to undergo surgical therapy, but the patient and family refused. It is necessary to think about endoscopic therapy in patients. Argon plasma coagulation (APC) has become the most widely used first-line endoscopic therapy.